ANALISIS KINERJA INDUSTRI KECIL MENENGAH (IKM) BATIK DI KOTA PEKALONGAN (PENDEKATAN STRUCTURE – CONDUCT – PERFORMANCE) - Rusda Arini, Dien; Sugiyanto, FX (Diponegoro Journal of Economics, 2013)
The small-medium enterprises (SME) of batik pekalongan having potensial contribution to the national income and to absorb labor force. Even though the globalization challenges, such as the agreement of ACFTA require the batik industy’s entrepreneur at Pekalongan city to compete with the batik’s design from other district. This situation increase the competition stricter and influence the market structure of pekalongan batik SME. Based on the Structure-Conduct-Performance (SCP) paradigm, to resist in the industry with the higher competition, companies in the industry have to execute some strategy (conduct) eventually affect that industy performance.The objective of this research are to identify the market structure of pekalongan batik’s SME in the SCP approach and to analize the relationship of structure, conduct, and performance on pekalongan batik SME in Pekalongan city. This research employed primary data that was obtained from 90 respondents through the questionare. The data was collected by Multistage Random Sampling. This research applied the descriptive analysis and invoked the Ordinary Least Square methode as the quatitative analysis.The results found that pekalongan batik SME have the monopolistic competition structure, with four largest companies concentration ratio (CR4) is 14,98% and HHI is 178,65. It means that companies have no power to increase price above the competitors, thereafter have the low performance. The result of regression analysis showed that structure have positif and significant affect on conduct with R2 is 0,671, and the conduct have positif and significant affect on performance with R2 is 0,593. Accordingly, relationship pattern of structure, conduct, and performance in pekalongan batik SME follow the Chain-Rule principle.